Framing of avian influenza coverage by Nigerian newspapers (2012)
The study examined framing pattern, direction of portrayal, space allotment and placement pattern in reporting avian influenza news in some selected Nigerian newspapers namely, The Guardian, Vanguard, Punch and Tribune were purposively selected between the periods of February 1st to August 31st 2006. Result showed that majority (52.56%) of avian flu disease stories were reported in the month of February and Guardian newspaper had the highest frequency of reports (69.2%). Analysis of the frames revealed that, public awareness (21.15%) was the most popular frame used. News on Avian Influenza and other Agricultural related issues had less placement patterns in most of the newspapers studied. The Vanguard newspaper had the highest frequency of reports on of avian flu on the front pages (23.1%), while the Guardian had the highest percentage (56.4%) of positive stories. There was no significant difference in space allotment among the selected newspaper (F = 0.526, P > 0.05). Similarly, there was no significant difference between space allotment and placement pattern (t = 0.40 p > 0.05). All the four selected newspapers stressed public awareness, Industry crisis and Government responsibility as national issues in reporting the cases of avian influenza in Nigeria.